Impact of the Serbian Banking Regulatory Framework Development on the Economic Growth of Serbia - Milojević, Nenad; Dimitrijević, Bojan (Industrija, 2013)
The dynamic relationship between the banking regulatory framework and Basel capital standards, on the one side and economic growth and other macroeconomic indicators on the other side, attracts international academic and business circles for many years. Perceived from the Serbian perspective, the impact of the banking regulation development, or the Basel standards application, on economic growth is one of the most actual issues, especially since Serbia starting from December 31st 2011, began the Basel II application. The fact that the National Bank of Serbia and the Serbian commercial banks, gradually directed attention to more actual Basel III standard, further increasing the importance of the topic that this paper will be addressed. Quantitative and qualitative analyzes that were performed during the research presented in this paper indicate a significant potential for further positive effects, including economic growth, due to the implementation of Basel standards in Serbia. Positive results of application largely depend on adequate preparation, analysis and actions of all relevant parties in Basel standards implementation.